2017
DOI: 10.15406/mojfpt.2017.04.00095
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in Rice, Their Role in Health Benefits

Abstract: Rice is a staple food for more than 60% of world population and it's the world's most consumed cereal. The rice grains contain many bioactive components as one of the major content which are the group of substances with beneficial health properties that are produced as secondary metabolites during grain filling. In rice flavonoids include tricin, luteolin, apigenin, quercetin, isorhamnetin, kaempferol and myricetin have human health benefits. This compound possesses many properties such as antioxidant, antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The cholesterollowering activity, anti-cancer, anti-oxidant of myricetin, tricin, apigenin, luteolin, quercetin, and isorhamnetin has been reported [24]. The anti-viral, anti-bacterial, anticancer, cardioprotective, and anti-inflammatory activity [76], as chelating agents and, are strong topoisomerase inhibitors [24] anti-aggregational, anti-atherosclerotic, and detoxification activities [77] of various flavonoids have been reported. These biological activities depend to a larger extent on the hydroxyl group in the flavonoids [78].…”
Section: Health Benefits Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholesterollowering activity, anti-cancer, anti-oxidant of myricetin, tricin, apigenin, luteolin, quercetin, and isorhamnetin has been reported [24]. The anti-viral, anti-bacterial, anticancer, cardioprotective, and anti-inflammatory activity [76], as chelating agents and, are strong topoisomerase inhibitors [24] anti-aggregational, anti-atherosclerotic, and detoxification activities [77] of various flavonoids have been reported. These biological activities depend to a larger extent on the hydroxyl group in the flavonoids [78].…”
Section: Health Benefits Of Flavonoidsmentioning
confidence: 99%
“…The protective effects such as the anti-inflammatory, anti-oxidant, anti-viral, and anti-tumor activity of flavonoids from natural sources are well documented [24]. The anti-carcinogenic activity of flavonoids has been linked to their anti-oxidant properties [25] which is due to the hydroxyl groups on the structure of the flavonoids [26].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research on liver drugs, not all medications can effectively treat individual levels and complications of liver disease [4] . Recent studies have shown that flavonoids, which are highly pharmacologically active compounds, possess antioxidant, anti-inflammatory, and antitumor properties and may be particularly beneficial in treating various liver diseases, including nonalcoholic fatty liver disease [5] , [6] , [7] , [8] . Additionally, flavonoids exhibit anticarcinogenic, antiviral, and immune stimulation properties [7 , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that flavonoids, which are highly pharmacologically active compounds, possess antioxidant, anti-inflammatory, and antitumor properties and may be particularly beneficial in treating various liver diseases, including nonalcoholic fatty liver disease [5] , [6] , [7] , [8] . Additionally, flavonoids exhibit anticarcinogenic, antiviral, and immune stimulation properties [7 , [8] , [9] , [10] . In a recent in vivo study, Xi Le and his team found that the flavonoid quercetin can improve liver inflammation and fibrosis by activating and polarizing hepatic macrophages in BALB/c mice [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that the development of dementia caused by Alzheimer's disease has a direct relationship with low consumption of flavonols: in people who had a high content of flavonols in the diet, the incidence of such dementia was 48% less [3]. It was also found that flavanols exhibit a modifying effect on hemoglobin, can be protectors and reducers in methemoglobin reactions that occur in erythrocytes, and can be used to prevent diabetic complications [11][12]. The flavonols quercetin, myricetin and rutin are stronger antioxidants than traditional vitamins.…”
mentioning
confidence: 99%